Malapportionment in space and time: Decompose it!. (June 2021) - Kamahara, Yuta; Wada, Junichiro; Kasuya, Yuko
Abstract: Existing studies on legislative malapportionment often conceptualize and measure this phenomenon with little regard to intertemporal variations and the malapportionment-generating process (MGP). Our conceptualization leads us to introduce a measure called α -divergence that can identify the vote inequality derived from various stages of MGP. Using an originally created database that covers 440 elections in 112 countries, we decompose the overall degree of malapportionment into three stages: malapportionment that arises at the stages of interstate apportionment, intrastate districting, and allotment of seats to special districts. We also provide analyses that can decompose the demographic and political factors contributing to the trends of the overall degree of malapportionment for selected countries.